2016
DOI: 10.1002/jbm.b.33735
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconduction in keratin-hydroxyapatite composite bone-graft substitutes

Abstract: Reconstituted keratin-hydroxyapatite (K-HA) composites have shown potential as nonload-bearing bone graft substitute material. This in vivo study investigated the bone regeneration response of keratin plus 40% HA composite materials in comparison to collagen counterparts and an unfilled defect site. The implantation site was a noncritical size defect created in the long bones (tibia) of sheep, with observations made at 1, 2, 4, 6, 8, and 12 weeks postimplantation. Porous K-HA materials displayed an excellent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…This biphasic combination can be considered as ideal for bone regeneration, since HA improves the mechanical behavior of the material in addition to slower resorption, while β‐TCP acts in the early stages of biomaterial remodeling favoring the onset of bone deposition (MacMillan, Lamberti, Moulton, Geilich, & Webster, ). This process is also known as creeping substitution mechanism where a bone substitute is characterized by its functionality during degradation and as an osteoconductive substrate (Dias et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This biphasic combination can be considered as ideal for bone regeneration, since HA improves the mechanical behavior of the material in addition to slower resorption, while β‐TCP acts in the early stages of biomaterial remodeling favoring the onset of bone deposition (MacMillan, Lamberti, Moulton, Geilich, & Webster, ). This process is also known as creeping substitution mechanism where a bone substitute is characterized by its functionality during degradation and as an osteoconductive substrate (Dias et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…45 Peplow et al 46 suggested that porous keratin matrices might be used as scaffolds in tissue repair or regeneration, while matrices with little or no porosity might serve to stabilize fractured bone or be used as bone anchors. Dias et al 47 subsequently implanted 3 mm diameter porous keratin cylindrical scaffolds containing 40% hydroxyapatite, into proximal condyle and mid-shaft sites in sheep tibia, with healing periods ranging from 1 to 12 weeks. New bone ingrowth reached the center of the cylinder by 4 weeks, however osteoid regeneration was 3 to 3.5 times slower than sham-operated unfilled control sites or defects filled with collagen.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27–29 ] Organic polymers consist of proteins such as: collagen, [ 30–32 ] gelatin, [ 33 ] elastin, [ 34 ] silk, [ 35 ] fibrin, [ 36,37 ] and keratin. [ 38 ] Polysaccharides such as chitosan, [ 39–41 ] hyaluronic acid, [ 42 ] alginic acid, [ 43,44 ] cellulose, [ 45,46 ] and chondroitin sulfate [ 47,48 ] are also commonly used. These materials usually demonstrate excellent biocompatibility and biodegradability.…”
Section: Requirements and Challengesmentioning
confidence: 99%